Sex differences and subclinical retinal injury in pediatric-onset MS - Graves, Jennifer S; Chohan, Hardeep; Cedars, Benjamin; Arnow, Samuel; Yiu, Hao; Waubant, Emmanuelle; Green, Ari (Multiple sclerosis, 2017)
To assess retinal ganglion cell (RGC) injury and sex differences in axon loss in pediatric multiple sclerosis (MS). This is a cross-sectional evaluation of consecutive pediatric MS subjects and controls. Eyes with acute optic neuritis (ON) within 6 months of visit were excluded. Spectral domain optical coherence tomography (OCT) included peripapillary ring and macular scans with post-acquisition segmentation of retinal layers using automated software (Heidelberg v1.8.6.0). Generalized estimating equations (GEEs) measured associations of sex, history of ON, disease duration, and age with OCT outcomes. In all, 53 MS subjects (100 eyes, median disease duration = 1.0 years, interquartile range (IQR) = 0.3, 2.5) were compared to 19 control subjects (38 eyes). Eyes with history of ON showed reduced retinal nerve fiber layer (RNFL: -26.8 µm, 95% confidence interval (CI) = -38.9, -14.8, p < 0.001) and 26% lower ganglion cell layer (GCL) volumes (-0.12 mm , 95% CI = -0.16, -0.072, p < 0.001) compared to control eyes. Non-ON MS eyes had lower temporal RNFL (-11.9 µm, 95% CI = -18.6, -5.3, p < 0.001) and GCL volumes (-0.036 mm , 95% CI = -0.06, -0.011, p = 0.004) than control eyes. In MS eyes, males versus females had lower global RNFL (-9.4 µm, 95% CI = -17.4, -1.33, p = 0.022) and in ON eyes had lower temporal quadrant RNFL (-9.6 µm, 95% CI = -15.1, -4.15, p = 0.001). Subclinical retinal injury occurs in pediatric-onset MS patients without a history of ON. As in adult-onset MS, substantial GCL thinning is present in eyes with prior ON. Finally, greater retinal axonal injury occurs in boys compared to girls.